A mechanism for enhanced symmetric key encryption based mixnet - Haddad, H.A.; Tsurugi, H.; Tamura, S. (2009 IEEE International Conference on Systems, Man and Cybernetics, 2009)
Anonymous networks enable entities to send messages without disclosing their identities. Many anonymous networks had been proposed already, such as Mixnet, DC-net, Crowds, etc. However, they still have serious drawbacks. Namely, they require tremendous computation overheads to transmit messages over networks. That is because asymmetric key encryption algorithms are used. This paper proposes a new mechanism for anonymous communication that removes these drawbacks while exploiting symmetric key encryption algorithms.